Educational Policy Strategy Under The Papua Special Autonomy Framework - Silo, Akbar (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2012)
An appropriate policy design is a crucial factor in improving the efficiency of education service. The design is influenced by the significant implementation of education strategies, to which the dimensions of organizational environment, organizational values, and organizational resources contribute. In the case of Jayapura Regency, the dimension that predominantly affects the education service efficiency is the organizational resources, whilst the organizational environment is the least influential. The small influence from the organizational environment results from a strong tendency to disregard the importance of politics, geography, demography, and the potential of natural resources as a dimension of the external environment. Moreover, the education service orientation and public needs accommodation are determined by the support from organizational values and resources.